« Le droit français aux prises avec les limites planétaires » - Luis Roman Arciniega Gil (Développement Durable et Territoires)
Planetary boundaries are a conceptual tool that aims to assess the capacity of the Earth to absorb anthropogenic pressures. The objective is to ensure a safe operating system for humanity based on ecological thresholds associated with nine biophysical processes that regulate the stability of the Earth as a whole. The colloquium "French Law and the Planetary Boundaries", held on 27 and 28 June 2022 at the University of Lille, called on specialists in environmental law to debate the subject and to take stock of the protection that the law offers to these ecological processes. This event, sponsored by the CNRS, the University of Lille, the Ceraps UMR 8026, the DD&T association, the RNMSH and the HDF region, was followed by political scientists, sociologists, lawyers, civil servants, public agents from local authorities, members of associations, students and researchers from different disciplines, which shows that the subject goes beyond the only academic and legal sphere.